Malaysian English: Exploring the Possibility of Standardization - Talif, Rosli; Hie, Ting Su (Universiti Putra Malaysia Press, 1994)
The notion of Malaysian English in relation to the concepts of standard English and language standardization is explored. An overview of the development of varieties of English spoken in Malaysia is discussed and the factors involved in language standardization such as the role of codifying agents in regulating the use of Malaysian English, the status of Malaysian English as a "New English", the need for a standardized variety of Malaysian English and the linguistic complexity of Malaysian English are examined. Of the three varieties of Malaysian English, namely, Malaysian English Type I, Malaysian English Type 11 and colloquial Malaysian English, Malaysian English Type II has the potential to develop into a widely accepted variety of Malaysian English. Nevertheless, the possibility of Malaysian English being standardized is still remote due to the limited need for a standardized variety of Malaysian English as the reference model in language teaching, and its early stage in the process of language standardization. Further and on-going descriptive studies on Malaysian English are needed.